BUDAYA KERJA PETANI TRANSMIGRAN SUKU JAWA DI DESA PURWODADI KECAMATAN MALIKU KABUPATEN PULANG PISAU - Sriyana Sriyana; Ijohn Indhie Saha (JURNAL SOCIOPOLITICO, 2022)
Work culture is a philosophy based on a view of life as values ​​that become the nature, habits and driving force, entrenched in the life of a community group or organization which is reflected from attitudes into behaviors, beliefs, ideals, opinions and actions that manifest as work or work. The purpose of this study was to describe the work culture and success tips of Javanese transmigrant farmers in Purwodadi Village, Maliku District, Pulang Pisau Regency. This study uses a qualitative research method with the object of farmer's work culture and the subject is the Javanese transmigrant community and the number of 10 people is determined by purposive sampling method. Data collection techniques through observation, interviews, and documentation as well as data validation using triangulation techniques. The results of this study indicate that the work culture of transmigrant farmers in Purwodadi Village, Maliku District, Pulang Pisau Regency is very good, namely hard working culture. While the tips for success according to the farming community are very diverse, namely work hard, be diligent, patient, honest, use the best time possible, make more friends, continue to learn about new things, have principles and don't let people get hurt and don't forget to pray.